2006
DOI: 10.1055/s-2006-931676
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular neoplasms induced by low-number pancreatic islet transplants in autoimmune diabetic BB/Pfd rats

Abstract: It has been shown that combined high local hyperinsulinism and hyperglycemia after low-number islet transplantation into the livers of streptozotocin-diabetic rats lead to the development of hepatocellular neoplasms but a substantial cocarcinogenic effect of genotoxic streptozotocin could not be ruled out completely. Thus, we herein investigated this model in BB/Pfd rats (n = 805; nine experimental groups), which develop spontaneous autoimmune diabetes similar to human type 1 diabetes. After low-number islet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 18 publications
6
52
2
Order By: Relevance
“…Details of animal treatment and transplantation procedures have been described . 14,16,20 Briefly, in the insulin model, Lewis rats (3 months old; body weight: 250-300 g) were made diabetic by injection of a single subcutaneous dose of streptozotocin (65 mg/kg body weight). Hormone deficiency in the T3 model was reached by thyroidectomy.…”
Section: Animal Treatment and Transplantation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of animal treatment and transplantation procedures have been described . 14,16,20 Briefly, in the insulin model, Lewis rats (3 months old; body weight: 250-300 g) were made diabetic by injection of a single subcutaneous dose of streptozotocin (65 mg/kg body weight). Hormone deficiency in the T3 model was reached by thyroidectomy.…”
Section: Animal Treatment and Transplantation Proceduresmentioning
confidence: 99%
“…This is a decisive prerequisite for the models to function and was carefully monitored by determining glucose and hormone blood levels as described. 14,16,20 If the systemic hormonal deficiency is secured, each transplanted endocrine tissue piece is permanently stimulated to maximally synthesize and secrete the respective hormone into the portal/sinusoidal blood. In this study we used animals between 1 and 12 weeks after transplantation, because at this time interval, the altered liver morphology was dependent only on primary effects of the grafts as previously shown 14,20 and was thus optimal for the purposes of this experiment.…”
Section: Animal Treatment and Transplantation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…It is intriguing, however, that separate research has shown that experimental hepatitis C infection is associated with downregulation of AMPK activity, and that restoring AMPK activation by metformininduced energy stress reduces viral infection and some of its consequences (16). Another example of interesting research in this context is evidence that insulin (which reaches the liver in high concentrations in the hyperinsulinemic phase of type II diabetes) is sufficient to induce liver cancer (17,18); thus, information concerning insulin levels and signaling downstream of the insulin receptor in the presence and absence of metformin in the model of Bhalla and colleagues (2) would be of interest. Another unanswered question is the relevance of the recently described metformin-induced inhibition of mitochondrial ROS production in vitro to step-wise carcinogenesis in vivo (4).…”
mentioning
confidence: 99%